2011
DOI: 10.1097/yic.0b013e32833e34d9
|View full text |Cite
|
Sign up to set email alerts
|

Extended release quetiapine fumarate (quetiapine XR) monotherapy as maintenance treatment for generalized anxiety disorder

Abstract: The objective of this study was to evaluate the efficacy and tolerability of extended release quetiapine fumarate (quetiapine XR) as maintenance monotherapy for patients with generalized anxiety disorder (GAD). Time-to-event (anxiety symptom recurrence; maximum 52 weeks) multicenter, randomized-withdrawal, parallel-group, double-blind, placebo-controlled study of quetiapine XR (50-300 mg/day) following open-label run-in (4-8 weeks) and open-label stabilization (≥ 12 weeks). Primary variable: time from randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 39 publications
4
73
0
Order By: Relevance
“…23 The extent of quetiapine use to treat anxiety is unprecedented for an antipsychotic. Although several small randomized trials 24,25 were completed and published earlier, the first large randomized controlled trial (RCT) of quetiapine for anxiety was published in a peer-reviewed journal in 2010 26 followed by 4 others [27][28][29][30] in the following years. A systematic review 31 of RCTs of quetiapine for anxiety found it to be clinically efficacious for generalized anxiety; however, its overall tolerability was poor.…”
Section: Discussionmentioning
confidence: 99%
“…23 The extent of quetiapine use to treat anxiety is unprecedented for an antipsychotic. Although several small randomized trials 24,25 were completed and published earlier, the first large randomized controlled trial (RCT) of quetiapine for anxiety was published in a peer-reviewed journal in 2010 26 followed by 4 others [27][28][29][30] in the following years. A systematic review 31 of RCTs of quetiapine for anxiety found it to be clinically efficacious for generalized anxiety; however, its overall tolerability was poor.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of anxiety comorbidity may have implications for treatment choice as well. For example, antipsychotic medications such as quetiapine, which have some evidence for efficacy in anxiety disorders, may be considered [55]. Anxiety symptoms occurring in the context of a primary psychotic or mood disorder may be initially dismissed as psychotic or mood symptoms or be missed altogether.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of randomised placebo-controlled relapseprevention studies in patients who have responded to previous 'open' acute treatment of varying lengths reveal a significant advantage for staying on active medication (agomelatine, duloxetine, escitalopram, paroxetine, pregabalin, quetiapine, venlafaxine, vortioxetine), when compared with switching to placebo, for periods of between 6-18 months (Baldwin et al, 2011bKatzman et al, 2011;Rickels et al, 2010). …”
Section: Longer Term Treatmentmentioning
confidence: 99%